Using Participatory Approaches to Enhance Women’s Engagement in Natural Resource Management in Northern Ghana - Cronkleton, P.; Evans, K.; Addoah, T.; Smith Dumont, E.; Zida, M.; Djoudi, H. (MDPI, 2021)
From 2016–2019, the West African Forest-Farm Interface (WAFFI) project engaged with smallholder farmers in northern Ghana to explore mechanisms to improve the influence of under-represented peoples, particularly women, in decision-making processes and platforms that affect their access to natural resources. Through a multi-phase process of participatory activities, including auto-appraisal, participatory action research (PAR) and facilitated knowledge exchange, villagers and researchers worked together to document and develop a better understanding of the challenges and changes facing women and men in the region to generate social learning. Among these challenges, the degradation of forest resources due to over exploitation, weak governance and conflict of use over shea trees (Vitellaria paradoxa) were particularly important for women. The WAFFI approach created a scaffold for social learning that strengthened the capacity of local stakeholders to share their perspectives and opinions more effectively in multi-stakeholder forums and dialogue related to resource use and land use change initiatives.